Analisis QoS Pengaplikasian Network Slicing Pada Topologi Abilene Jaringan SDN Menggunakan FlowVisor Dan POX Controller - Putra, Fadly Firmansyah; Dewanta, Favian; Naning Hertiana, Sofia (MULTINETICS, 2023)
Software Defined Network (SDN) is a new paradigm in computer networks that separates the data plane and the control plane. With this separation, network configuration will be easier to do, not as complicated as conventional networks. This research discusses how to implement the network slicing method using FlowVisor on the SDN network with POX as the controller. Network slicing allows each network slice to be designed to guarantee different levels of network performance. The emulator used to design the topology as well as the data plane is Mininet. The results of this researchs indicate that FlowVisor can isolate flowspace for each slice on the SDN network based on the TCP port that is passed when communication occurs between hosts. Comparison of SDN networks without using the network slicing method with SDN networks using the network slicing method produces values that are not much significant, but the QoS parameter values are better on SDN networks without network slicing. Throughput on 1 Mbps link bandwidth is 0.8 Mbps, slow slice 0.79 Mbps, on 10 Mbps link bandwidth is 7.4 Mbps, fast slice is 6.6 Mbps. Delay on 1 Mbps link bandwidth is 1.361 ms, slow slice 1.389 ms, on 10 Mbps link bandwidth 0.155 ms, fast slice 0.2426 ms. Jitter on 1 Mbps link bandwidth is 0.000283 ms, slow slice 0.000257 ms, on 10 Mbps link bandwidth 0.0000304 ms, fast slice is 0.0000347 ms.